'How to do': digital-interactive-interpretation course for stress echocardiography. Issue 1 (20th January 2021) - Kardos, Attila; Schaupp, Ramona; Kettner, Lillian; Becher, Harald
Abstract: Why?: To improve stress echocardiography interpretation standards, we introduced a structured 5-day interpretation course in 2017. In order to deliver the course during the world-wide pandemic, we transformed the existing boardroom style, workstation-based, interactive course into a cloud-based digital entity maintaining the same features. How?: On completion of 6 lectures via live webinars, 15 participants performed, fully GDPR compliant, 80 recorded case analysis using a web-based reporting system over the course of 5 days. After self-reporting and generating preliminary reports the joint case review with the faculty, resulted in finalization of the reports and provided individual feedback for the participants. By the 5th day, participants had collected 80 reports for their e-logbook and were ready to sit the digital interpretation exam. Results: Eighty-eight percent of participants passed the e-exam and received a certificate of completion with 15 re-accreditation and 30 CPD points by the British Society of Echocardiography and Federation of the Royal Colleges of Physicians, UK, respectively. The feedback by the participants was praising the pre-course provision of lectures and digital aids, the conduct of the course by the faculty and the technical support with an average score of 4.7 for each, on a scale from 1 to 5. Conclusion: Our experience proved that interactive, multi-day; hands-on reporting course can be delivered using the digital platform. Online interpretation courses have great potential to improve the competency of imaging specialists. This digital teaching model could be suitable in other imaging-based training courses like cardiac CT and MRI. Graphical Abstract: